Prevalence of atrial septal defects and patent foramen ovale in a cohort of sudden cardiac death patients undergoing autopsy - Fahy, Louise; Rowe, Stephanie; Nehme, Ziad; Stub, Dion; Zentner, Dominica; James, Paul; Pflaumer, Andreas; Connell, Vanessa; Semsarian, Christopher; Ingles, Jodie; La Gerche, Andre; Paratz, Elizabeth D. (Journal of cardiology, 2024)
Patent foramen ovale (PFO) and atrial septal defects (ASD) have been described in up to 30 % of subjects in autopsy series but contemporary data are scarce. It is important to confirm the prevalence of ASD/PFO in the general population given the potential associated stroke risk and the increasing availability of intervention via PFO closure. A state-wide prospective out-of-hospital cardiac arrest registry (OHCA) identified all patients aged 1 to 50 years who experienced OHCA in Victoria, Australia from April 2019 to April 2022 and subsequently underwent autopsy with a cardiac cause of death identified. Autopsy was performed including visual description of any ASD and identification of probe patency of foramen ovale. A total of 517 patients underwent autopsy in the setting of sudden cardiac death; 36 patients (6.9 %) had a probe-patent foramen ovale, 2 patients (0.4 %) had secundum ASD, and 2 patients (0.4 %) had both a PFO and ASD (1 of whom had undergone percutaneous repair of both lesions). Twelve patients (2.3 %) had a prior history of cerebrovascular accident either recorded on medical history or detected on neuropathological examination; however none of these patients had a PFO or ASD. The combined rate of PFO and ASD in a cohort of 517 patients undergoing autopsy was 7.9 %. None of these patients had experienced a cerebrovascular accident. This rate of PFOs appears lower than earlier reports and raises the possibility that the relative risk of an associated stroke could be higher than previously estimated. [Display omitted] •Patent foramen ovale (PFO) can be associated with young cryptogenic stroke.•PFO prevalence in young cryptogenic stroke patients can be up to 45 %.•In our sudden cardiac death autopsy cohort, PFO rate was 7.4 %.•This lower PFO rate increases PFO's overrepresentation in cryptogenic stroke.